Degree of pulmonary fissure completeness can predict postoperative cardiopulmonary complications and length of hospital stay in patients undergoing video-assisted thoracoscopic lobectomy for early-stage lung cancer. (11th August 2017) - Li, Shuangjiang; Zhou, Kun; Wang, Mingming; Lin, Rongjia; Fan, Jun; Che, Guowei
Abstract: OBJECTIVES: To estimate the effects of pulmonary fissure completeness on postoperative cardiopulmonary complications (PCCs) and hospital stay in patients undergoing video-assisted thoracoscopic surgery lobectomy for early-stage non-small-cell lung cancer. METHODS: We performed a single-centre retrospective analysis based on the prospectively maintained data of our institution during the study period. Demographic differences between the PCC group and the non-PCC group were initially examined. Then, the patients were classified into 3 groups according to their fissure sum averages (FSAs: 0 ≤ FSA ≤ 1, 1 < FSA ≤ 2, 2 < FSA ≤ 3) calculated by fissure development scores. The differences in PCC incidences and hospital stay between these 3 groups were further evaluated. Finally, FSA > 1 was determined as the cut-off to indicate the degree of pulmonary fissure completeness and involved into a multivariate logistic regression model to identify the predictors for PCCs. RESULTS: In total, 528 patients with Stage I to Stage II non-small-cell lung cancer were enrolled. There were 343 patients with 0 ≤ FSA ≤ 1, 105 patients with 1 < FSA ≤ 2 and 80 patients with 2 < FSA ≤ 3. Pulmonary complication rate in patients with 1 < FSA ≤ 2 (25.7% vs 14.3%; P = 0.006) and with 2 < FSA ≤ 3 (33.8% vs 14.3%; P < 0.001) was significantly higher than that in patients with 0 ≤ FSA ≤ 1. No difference was found in cardiovascular complication rate between these groups ( P = 0.22). The Kaplan–Meier analysis showed that the length of hospital stay and the length of chest tube drainage in patients with 1 < FSA ≤ 2 and with 2 < FSA ≤ 3 were significantly longer than those in patients with 0 ≤ FSA ≤ 1. Incomplete pulmonary fissure (FSA > 1) was a strong independent predictor for PCCs (odds ratio = 2.12; P = 0.002) in the multivariate analysis. CONCLUSIONS: The degree of pulmonary fissure completeness can predict the PCCs and the length of hospital stay following video-assisted thoracoscopic surgery lobectomy for early-stage non-small-cell lung cancer.